Structural analysis and optimization for ITER upper ELM coil - Zhang, S.W.; Song, Y.T.; Wang, Z.W.; Du, S.S.; Ji, X.; Liu, X.F.; Feng, C.L.; Yang, H.; Wang, S.K.; Daly, E.; Kalish, M. (Fusion engineering and design, 2014)
•The updated structure of ITER upper ELM coil is introduced and thermal, static and fatigue analyses are performed to obtain its temperature distribution and verify its structural integrity.•Structural optimization for upper ELM coil proves that adding fillet, increasing the thickness of the connecting plate of the bracket and lowering the connecting plate for the bracket are needed in order to increase the strength of bracket.•To enhance the fatigue performance of jacket, the reinforcement and spine is proposed.•After the above efforts, the stress of the IMIC can meet the static and fatigue criteria and this means the basic structure is valid. ITER ELM coils are used to mitigate or suppress Edge Localized Modes (ELM), which are located between the vacuum vessel (VV) and shielding blanket modules and subject to high radiation levels, high temperature and high magnetic field. These coils shall have high heat transfer performance to avoid high thermal stress, sufficient strength and excellent fatigue to transport and bear the alternating electromagnetic force due to the combination of the high magnetic field and the AC current in the coil. Therefore these coils should be designed and analyzed to confirm the temperature distribution, strength and fatigue performance in the case of conservative assumption. To verify the design structural feasibility of the upper ELM coil under EM and thermal loads, thermal, static and fatigue structural analysis have been performed in detail using ANSYS. In addition, design optimization has been done to enhance the structural performance of the upper ELM coil.